2023
DOI: 10.1080/15548627.2023.2246356
|View full text |Cite
|
Sign up to set email alerts
|

Lactate is a bridge linking glycolysis and autophagy through lactylation

Abstract: Lactate is a glycolysis product that is produced from pyruvate by LDH (lactate dehydrogenase) and plays an important role in physiological and pathological processes. However, whether lactate regulates autophagy is still unknown. We recently reported that LDHA is phosphorylated at serine 196 by ULK1 (unc-51 like kinase 1) under nutrient-deprivation conditions, promoting lactate production. Then, lactate mediates PIK3C3/VPS34 lactylation at lysine 356 and lysine 781 via acyltransferase KAT5/TIP60. PIK3C3/VPS34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
6
1
Order By: Relevance
“…Many studies had confirmed that cells utilize glucose mainly through glycolysis, aerobic oxidation and glycogen synthesis, and lactate was one of the metabolic products of glycolysis ( Sun et al, 2023 ). In our lactate content determination experiments, the cells were cultured under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies had confirmed that cells utilize glucose mainly through glycolysis, aerobic oxidation and glycogen synthesis, and lactate was one of the metabolic products of glycolysis ( Sun et al, 2023 ). In our lactate content determination experiments, the cells were cultured under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that LDHA regulated lactate production to in uence histone lysine lactylation and acetylation [33][34][35] . Here, we observed that the levels of lactylated histone H3K18 (H3K18Lac) and acetylated H3K18 (H3K18Ac) were increased in Th1 cells differentiation with poly(I:C) stimulation compared with mock control (Fig.…”
Section: Rig-i De Ciency Relieved Eae Mice Model and Lupus-like Mice ...mentioning
confidence: 99%
“…It has also been suggested that high lactate mediates PIK3C3/VPS34 emulsification and induces autophagy, thereby promoting cancer progression. Lactate is a bridge linking glycolysis and autophagy [ 127 ]. Furthermore, canagliflozin (CAN) can inhibit glucose uptake and lactate release, and modulate autophagy at the same time, thus enhancing the radiosensitivity of HepG2 cells.…”
Section: Mechanisms Underlying Radioresistance Due To Hypoxia and Met...mentioning
confidence: 99%